Peluang Penerapan Beyond Budgeting sebagai Upaya Optimalisasi Manajemen Perusahaan Studi Kasus PT Asuransi Jasindo Syariah - Apriandi, Muhammad Rifky (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The insurance sector is important for the Indonesian economy. Insurance companies must be able to manage their budget well and precisely because otherwise it will result in company losses. Budgeting discrepancies will result in insurance companies having difficulty achieving financial targets, including providing claims. Therefore, this research aims to find out the comparison of the concepts of traditional budgeting and beyond budgeting and how company management performs using traditional budgeting. Apart from that, this research aims to find out how prepared the company is to implement beyond budgeting. This research is a qualitative research involving case studies conducted at PT. Jasindo Syariah Insurance. The data collection techniques used in this research include semi-structured interview techniques and data triangulation. Of the total of 12 beyond budgeting principles, the level of implementation varies. The Anticipation System principle has been implemented throughout the company. The principles of Governance, Accountability for Dynamic Results, Organizational Networks, Relative Targets and Resource Allocation have been partially implemented by the company. On the other hand, the principles of Manager Empowerment, Market Coordination, Supportive Leadership, Continuous Strategy Determination, Speed ​​of Information Distribution and Rewards are relatively small which have been implemented by companies. The research findings highlight the significant potential beyond budgeting for Jasindo Syariah Insurance Company. Keywords: Beyond budgeting, traditional budgeting.